(untitled) (Journal of International Studies, 2018)
In light of the recent waves of secessionist struggle and conflict in Africa, a number of debates have spurred the possibility of secession outside the colonial context. Sourcing data from documentary materials coupled with the application of historical methods of data analysis, this article reflects on Eritrea’s secession from Ethiopia in 1993. The study discusses and argues that Eritrea’s feat in 1993 was made possible by certain domestic and external factors that did not present themselves to earlier secessionist movements. It concludes that without those factors that made Eritrea secession possible for its re-invention, furthermore, given that the forces that propelled the 1964 Cairo Agenda are still alive and formidable, secession outside the colonial context in Africa is likely to remain a difficult endeavor.